Ukrainian Private Law and the European Area of Justice - Kurzynsky-Singer, Eugenia; Kulms, Rainer (Mohr Siebeck, 2019)
The present collection of essays addresses the development of Ukrainian private law in the course of its ongoing Europeanization. This process is determined by the Association Agreement between the EU and Ukraine, which was concluded in 2014 and obliges Ukraine to implement a diverse number of European legal acts in its national legal system, aiming to achieve the economic integration of Ukraine into the EU internal market. Nevertheless, it would be inaccurate to describe the process of integrating Ukrainian private law into the European Area of Justice as solely the implementation of the Community acquis. Rather, the Europeanization of Ukrainian private law is part of a value-based Europeanization of the entire Ukrainian society.